Block Copolymer Synthesis by the Combination of Living Cationic Polymerization and Other Polymerization Methods - Dey, Asmita; Haldar, Ujjal; De, Priyadarsi (Frontiers in Chemistry, 2021)
The key limitation of block copolymer synthesis is to polymerize two or more different monomers having discrete reactivity profile using one single polymerization technique. Controlled living polymerization techniques play a pivotal role in the synthesis of endless new block copolymers, thus are revolutionary techniques for the preparation of complex macromolecular frameworks. Polymers with predetermined average molecular weight, narrow dispersity, chain-end functionality, and architectures can be prepared by these processes. In order to improve the existing applications and create new opportunities to design a new block copolymer system with improved physical and chemical properties, the combination of two different polymerization techniques have tremendous scope. Such kind of macromolecules may be attended by combination of homopolymerization of different monomers by post-modification techniques using macroinitiator or by using dual initiator which allows mixing of two mechanistically unique polymerization techniques. This article emphasizes on recent successes in block copolymer preparations by combination of polymerization techniques, specifically living cationic polymerization with other controlled polymerization techniques and “click” chemistry.